Dendrite coherency point of A357 alloys - 李建峰 寇宏超 王安家 李金山 胡锐 傅恒志 (Transactions of Nonferrous Metals Society of China, 2006)
The dendrite coherency point was determined for A357 alloys using double-thermocouples technique. The effects of the cooling rate and different treatments such as grain refinement, modification, and superheat on the dendrite coherency point were investigated. The results show that the increase of the cooling rate and refinement significantly postpones the coherency point of A357 alloys. The morphology of silicon phase is modified, which slightly leads to lower solid fraction （fs） at the coherency point. But the fs^coh value decreases after superheat treatment at 850 ℃ for 30 min. The grain size plays a decisive role in the fs^coh value ofA357 alloys. The smaller the grain size is, the more the fs^coh value increases, which is beneficial to improving the final property of this alloy, while the secondary dendrite arm spacing and modification have almost no influence on fs^coh.